A Study on IoT based m-Health Systems for Diabetes (International Journal of Innovative Research in Computer Science & Technology, 2022)
This article provides an overview of the  newest mobile health apps based on Internet of Things that  are utilized for diabetes control. Diabetic is a group of  metabolism illnesses characterized by persistently increased  glucose content. Long-term hyperglycemia management  requires the involvement of individuals, doctors, and familial  careers. With rapid advancements in cellular and network  technologies, a range of World wide web of Things-based  solutions for diabetic’s management have already been  proposed. The majority of these apps are focused on medical  observation and technology-assisted selection. We look at  how these new applications work and their basic technology,  as well as the major issues and difficulties they face. The  major goal of this paper is to aid academics in the  development of better diabetic management applications.
Keywords: Diabetes; Disease; Disorders; Health; Metabolic